Ultrathin and flexible sensors for pressure and temperature monitoring inside battery cells - Dreher, Vincent; Joch, Daniel; Kren, Harald; Schwarberg, Jannik; Jank, Michael P.M. (Proceedings of IEEE Sensors, 2022)
Accurate in situ monitoring of crucial parameters like temperature and pressure lead to a better understanding of processes that occur in a battery through its lifetime and therefore accelerate the development of new technologies in the battery market. This paper presents an integration scheme for ultrathin temperature and pressure sensors on a flexible sheet using common thin-film processing. The sensors cover the specific detection ranges (up to T = 80 °C, p = 1.5 MPa) and sensitivities for the envisioned application. Furthermore, it is shown that the dedicated encapsulation and flat topology do not influence the electrochemical performance of the battery cell.
Created from Fastlane, Scopus look-up
Keywords: battery technology; flexible substrate; pressure sensor; temperature sensor; thin film technology